2015
DOI: 10.1007/s13277-015-4586-5
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Clinical significance and expression of the PRSS3 and Wiskott–Aldrich syndrome protein family verprolin-homologous protein 1 for the early detection of epithelial ovarian cancer

Abstract: In this study, we evaluate the clinical significance of the PRSS3 and Wiskott-Aldrich syndrome protein family verprolin-homologous protein 1 (WAVE1) in patients with epithelial ovarian cancer (EOC) by immunohistochemistry.In current study, all adjacent non-cancerous tissues showed absent or low expression of PRSS3. The expression of PRSS3 was significantly increased in the EOCs than adjacent non-cancerous tissues. Moreover, the expression of WAVE1 was significantly observed in all EOC tissues when compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…6 Trypsin belongs to the serine protease family and was recently found to be an important driver in several pathophysiological context including cancer initiation. 7 It was acknowledged that trypsin was derived from the trypsinogen, which was synthesized in the pancreas as an inactive precursor and then activated in the gastrointestinal tract. 8 And the cancer-related synthesis of trypsinogen has been identified in various types of tumor, which was indicated to be essential for carcinogenesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 Trypsin belongs to the serine protease family and was recently found to be an important driver in several pathophysiological context including cancer initiation. 7 It was acknowledged that trypsin was derived from the trypsinogen, which was synthesized in the pancreas as an inactive precursor and then activated in the gastrointestinal tract. 8 And the cancer-related synthesis of trypsinogen has been identified in various types of tumor, which was indicated to be essential for carcinogenesis.…”
mentioning
confidence: 99%
“…It has been previously reported that dysfunction of serine proteases might contribute to the development of malignant tumors 6. Trypsin belongs to the serine protease family and was recently found to be an important driver in several pathophysiological context including cancer initiation 7. It was acknowledged that trypsin was derived from the trypsinogen, which was synthesized in the pancreas as an inactive precursor and then activated in the gastrointestinal tract 8.…”
mentioning
confidence: 99%
“…PRSS3 was expressed in both ovarian epithelial cancer and benign ovarian tumors, but its expression was significantly higher in ovarian epithelial cancer [3132]. Hockla et al [3336].…”
Section: Discussionmentioning
confidence: 99%